2007
DOI: 10.1038/sj.npp.1301308
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and Heroin Differentially Modulate In Vivo Hippocampal LTP in Opiate-Dependent Rat

Abstract: Addictive drugs have been shown to severely influence many neuronal functions, which are considered as the underlying mechanisms for physiological and psychological dependences. We previously showed that in vivo LTP in rat hippocampal CA1 region is significantly reduced during withdrawal following chronic opiates treatment, and the reduced LTP can be restored by re-exposure of animals to corresponding drugs. Here, we further demonstrated that during opiates withdrawal, the re-exposure of morphine either system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 78 publications
(88 reference statements)
0
47
0
1
Order By: Relevance
“…It is worth noting, however, that reductions in NAc core A/N ratios due to up-regulation of NR2B-containing NMDAR currents have been reported following heroin self-administration in rats, and that this adaptation drives reinstatement of heroin seeking (24). The mechanisms underlying this apparent discrepancy in plasticity are unclear; however, morphine and heroin have been shown to differentially modulate synaptic strength (44). Furthermore, distinctions in learning and motivational processes associated with operant responding tasks vs. CPP, as well as incorporation of extinction vs. abstinence following drug exposure may be contributing factors to these differences.…”
Section: Prefer Test Pre-testmentioning
confidence: 76%
“…It is worth noting, however, that reductions in NAc core A/N ratios due to up-regulation of NR2B-containing NMDAR currents have been reported following heroin self-administration in rats, and that this adaptation drives reinstatement of heroin seeking (24). The mechanisms underlying this apparent discrepancy in plasticity are unclear; however, morphine and heroin have been shown to differentially modulate synaptic strength (44). Furthermore, distinctions in learning and motivational processes associated with operant responding tasks vs. CPP, as well as incorporation of extinction vs. abstinence following drug exposure may be contributing factors to these differences.…”
Section: Prefer Test Pre-testmentioning
confidence: 76%
“…In addition, previous studies have shown that hippocampal LTP is reduced by chronic morphine treatment (Pu et al, 2002;Bao et al, 2007). Based on these findings, we therefore determined whether the extracellular adenosine accumulation could contribute to the impairment of LTP by activation of adenosine A 1 receptors in response to chronic morphine treatment.…”
Section: Accumulation Of Extracellular Adenosine Concentration Inhibimentioning
confidence: 99%
“…Accumulating evidence demonstrates that it also plays a role in opioid dependence (Done et al, 1992;Fan et al, 1999;Lu et al, 2000;Rezayof et al, 2003). Several studies have shown that chronic exposure to morphine or heroin leads to the impairment of hippocampal LTP (Pu et al, 2002;Salmanzadeh et al, 2003;Bao et al, 2007) and induces cognitive deficits, as shown by poor performances on memory task of heroin abusers (Guerra et al, 1987) or chronic opiatetreated rodents (Spain and Newsom, 1991;Li et al, 2001;Pu et al, 2002;Miladi Gorji et al, 2008). However, the mechanisms underlying these effects of opiates are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…57 Similarly, it is now well known that there is intense interest in the role of stem cells in the adult brain, particularly with reference to function in memory [69][70][71] and emotional stability, [72][73][74][75] two areas which are particularly vulnerable in drug addiction. [76][77][78] A focus on cellular health, growth renewal and replication as is suggested in general terms by this report explains several seeming paradoxes in addiction medicine, such as a fi nding that on a genome-wide screen for genes up-regulated in addiction, genes corresponding to synapse formation, intracellular signalling and transcription factors were found to be most signifi cantly altered 79 and have been specifi cally identifi ed in studies of brain ageing. 80 Cortical regions such as the prefrontal lobes, the right inferior frontal gyrus, the dorsolateral prefrontal cortex, the anterior cingulate and the deep white matter of the frontal lobes, well known to be impaired in addiction, 54,55 have also been identifi ed as sites particularly vulnerable to age-related declines.…”
Section: Discussionmentioning
confidence: 70%